Ensuring the conditions of ecological safety of the surface water of Ukraine by calculating the values of their assimilative capacity - Kulikova, Daria V.; Yurchenko, Anneta A. (КНУБА, 2019)
The values of discharge of circulating (waste) waters of different quality categories in surface water objects by regions of Ukraine are analyzed. For maintaining the natural equilibrium of aquatic ecosystems the indicators of actual and limit necessary of the multiplicity of dilution of circulating (waste) waters of different quality categories by local river runoff are calculated and analyzed. The values of the limit assimilative capacity of surface water objects, which can accept a certain amount of circulating (waste) waters without violating their ecological stability, is determined. The characteristics of the level of assimilative capacity utilization of local river runoff resources of different degrees of water availability are calculated and given. It has been established that in the years with average water availability the level of use of the assimilative capacity of local river runoff resources of the Nikolaev, Kharkiv and Kherson regions is characterized as “moderate”, and Odessa – as “high”. In the years with a very low river water content, the level of use of the assimilative capacity of surface water bodies in Kiev, Kirovograd, Luhansk, Lviv, Sumy and Cherkasy regions is rated as “moderate”, Mykolaiv and Kharkiv – as “high”, Kherson and Odessa – as “very high”. Regardless of the level of provision with local river runoff, the index of the use of the assimilative capacity of water resources in Zaporizhia, Donetsk, and Dnipropetrovsk regions exceeds the threshold value (IAC = 1) by 10.35–99 times.
Забезпечення умов екологічної безпеки поверхневих водойм України шляхом розрахунку величин їх асиміляційної ємності
Keywords: assimilative capacity; environmental safety; self-cleaning; wastewater; surface water; multiplicity of wastewater dilution; асиміляційна ємність; екологічна безпека; самоочищення; стічні води; поверхневі водойми; кратність розбавлення стічних вод; 504.4.062.2